Answer:
{x,y} = {-2,-3}
Step-by-step explanation:
System of Linear Equations entered :
[1] -9x + 4y = 6
[2] 9x + 5y = -33
Graphic Representation of the Equations :
4y - 9x = 6 5y + 9x = -33
Solve by Substitution :
// Solve equation [2] for the variable y
[2] 5y = -9x - 33
[2] y = -9x/5 - 33/5
// Plug this in for variable y in equation [1]
[1] -9x + 4•(-9x/5-33/5) = 6
[1] -81x/5 = 162/5
[1] -81x = 162
// Solve equation [1] for the variable x
[1] 81x = - 162
[1] x = - 2
// By now we know this much :
x = -2
y = -9x/5-33/5
// Use the x value to solve for y
y = -(9/5)(-2)-33/5 = -3
Answer:
(1, –5)
Step-by-step explanation:
It is relatively easy to try the offered solutions to see what works.
<u>(1, -5)</u>
3(1) +10(-5) = -47 . . . true
5(1) -7(-5) = 40 . . . true
(1, -5) is the solution
_____
As a check, you can try some of the other choices:
<u>(1, 5)</u>
3(1) +10(5) ≠ -47
<u>(-1, -5)</u>
3(-1) +10(-5) ≠ -47
<u>(-1, 5)</u>
3(-1) +10(5) ≠ -47
None of the other choices works in the first equation, so they're not the solution.
Answer:
6 teaspoons
Step-by-step explanation:
PLz brainliest,Hope I could help
The formula for calculating compound interest with yearly contributions is:
Balance = X*(1 + Y)^n + Z((1 + Y)^(n + 1) - (1 + Y)/Y)
where the balance is the money earned after n years invested
Y is the interest rate as a fraction
Z is the yearly contribution
X is the starting investment
Therefore the calculation for this example is:
Balance = 1200*(1 + 0.05)^48 + 1200((1.05)^49 - (1.05)/05)
= $249,393.5
The answer is 27, I had it on a test.